Impact of National Social Intervention Programme (Nsip) on Women and Youths Empowerment in Nigeria - Musa, Zakari; Eyanuku, Julius; Mavis, Madu; Ubale Yahaya, Jibril (Acta Universitatis Danubius. Administratio, 2023)
The study examined the role of National Social Intervention on women and youth’s empowerment in Nigeria. Empowerment theory propounded by Solomon, (1976) was adopted as theory framework. The study adopted survey and documentary research design. The population of this study comprises of N-Power Volunteer Corps, public primary school Teachers, N-power officials, public primary school Pupils and vulnerable Nigerians that benefited from conditional Cash Transfer. Purposive, stratified and simple random sampling technique was used to select a representative from the entire population. Two method of data collection was utilized; primary method and secondary method. The survey used a combination of questionnaires and in-depth interviews to account for the wide range of experiences and viewpoints among respondents. Stratified and simple random sampling was used to select a representative sample from the larger population. The total population is 137,600,000 consisting of N-Power Volunteer Corps, N-power Build, and N-power Knowledge and Women. Two statistical techniques of data analysis were utilized; they are descriptive and inferential statistical techniques: The descriptive statistics will be used to present and interpret quantitative data. Descriptive statistics are; frequency table, percentage and figure. The Statistical Package for the Social Sciences (SPSS) was used to present and analyze the data. Out of the three hundred and seventy-eight (378) questionnaire distributed to the N-power beneficiaries in Nigeria, only three hundred and thirty-five (335) representing (89%) were duly completed and returned while Forty-three (43) (11%) were missing. In the same vein, out of the three hundred and eighty-four (384) questionnaires distributed to the Teachers Public Primary in Nigeria, only three hundred and thirty one (331) representing (86%) were duly completed and returned while fifty-four (54) representing (14%) were missing. Finding from the study revealed that, -power Programme as actually empowered unemployed graduate in Nigeria. N-power scheme have engaged graduate in four sectors of Nigerian Economy. These include; education, health, tax and agriculture. The temporary engagement of graduate in the scheme has led to proficiency skills in ICT, financial empowerment, on the job experience, investment in small scale businesses and above all reduced poverty in Nigeria. The study also revealed that, N-power build and knowledge has not contributed to poverty reduction in Nigeria. Youth trained on vocational skill were not empowered at the end of the training. This means that, all these efforts have not been translated into employment generation for self-reliance. The study further revealed that, finding from the analysis revealed that, Home Grown School Feeding of the Federal Government have empowered women, farmers as well as well-being of public primary school children in Nigeria. It was equally revealed that, about 14,000 vulnerable Nigeria are benefiting from Conditional Cash Transfer Scheme in Nigeria. Five (5,000) thousand is been paid monthly to poorest of the poor in every community in Nigeria and every payment is done through the beneficiary’s bank account.